Consumption of dairy and meat in relation to breast cancer risk in the Black Women’s Health Study - Genkinger, Jeanine M. (2013)
PURPOSE: Dairy and meat consumption may impact breast cancer risk through modification of hormones (e.g., estrogen), through specific nutrients (e.g., vitamin D), or through products formed in processing/cooking (e.g., heterocyclic amines). Results relating meat and dairy intake to breast cancer risk have been conflicting. Thus, we examined the risk of breast cancer in relation to intake of dairy and meat in a large prospective cohort study. METHODS: In the Black Women’s Health Study, 1,268 incident breast cancer cases were identified among 52,062 women during 12 years of follow-up. Multivariable (MV) relative risks (RRs) and 95 % confidence intervals (CIs) were calculated using Cox proportional hazards models. RESULTS: Null associations were observed for total milk (MV RR = 1.05, 95 % CI 0.74–1.46 comparing ≥1,000–0 g/week) and total meat (MV RR = 1.04, 95 % CI 0.85–1.28 comparing ≥1,000 <400 g/week) intake and risk of breast cancer. Associations with intakes of specific types of dairy, specific types of meat, and dietary calcium and vitamin D were also null. The associations were not modified by reproductive (e.g., parity) or lifestyle factors (e.g., smoking). Associations with estrogen receptor (ER) positive (+), ER negative (−), progesterone receptor (PR)+, PR−, ER+/PR+, and ER−/PR− breast cancer were generally null. CONCLUSIONS: This analysis of African-American women provides little support for associations of dairy and meat intake with breast cancer risk.